HYDATIDIFORM MOLE: A STATISTICAL SURVEY IN WEST OF IRAN - Shobeiri, Fatemeh; Aghababaii, Soodabeh; Hosseinipanah, Syed Mohammad (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the incidence of hydatidiform mole in west of Iran. Methodology: This study was carried out on pregnant women referring for delivery in Hamadan province in west of Iran. We retrospectively evaluated medical records of all referring subjects to medical centers in Hamadan prov-ince between 1997 and 2006. All pregnant women referred to 11 referral hos -pitals as well as obstetric care facility centers in the province were studied. We recorded all cases with hydatidiform mole. Data Processing and statistical analysis were performed using SPSS version 16.0. Results: The incidence of hydatidiform mole in Hamadan province estimat -ed 3.34 per 1000 pregnancies Between 1997 and 2006. It means 1 per 298.2 pregnancies had hydatidiform mole. The incidence rate of hydatidiform mole was considerably higher compared to reported from Japan, Turkey, Europe, USA, UK, China, Malaysia, whereas was lower than reported from Indonesia and India. The risk of recurrence rate of mole was higher than that reported in the UK, but lower than that shown in South Africa. Conclusion: The incidence of hydatidiform mole in Hamadan province of Iran seems to be high. Therefore early and rapid diagnosis of gestational tropho -blastic diseases in this region is strongly recommended.